SHAROF RASHIDOV’S ACTIVITIES AS CHAIRMAN OF THE PRESIDIUM OF THE SUPREME SOVIET OF THE UZBEK SSR (1950–1959) - Sulaymanova Shokhsanam Absamatovna (Web of Journals Publishing, 2025)
This article explores the activities of the supreme governing body of the Uzbek SSR the Supreme Soviet during the 1950s. The author analyzes the sociopolitical work of Sharof Rashidov, who served as Chairman of the Presidium of the Supreme Soviet of the Uzbek SSR from 1950 to 1959. Special attention is given to the tensions in “Center Republic” relations and to the transformations in the sphere of state governance during the period under study.
Keywords: governing body, Supreme Soviet, Communist Party, Council of Ministers, Presidium, collegial, president, Soviets, session, executive committees, citizen appeals.